Perbandingan Penafsiran tentang Pesan Moral Kisah Nabi Yusuf dalam Tafsir Al-Misbah dan Tafsir An-Nur (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The main problem in this research is formulated as a comparison of the interpretation of the moral message of the story of the prophet Yusuf in tafsir al-Misbah and tafsir an-Nur. This research is based on a literature review that uses various books found in libraries and digital that can be accessed easily. The results of this study are Moral Messages of the Story of the Prophet Yusuf in Tafsir Al-Misbah and Tafsir An-Nur focusing on Justice and Wisdom, Patience and Trust in Allah, Integrity and Piety, and Competence and Courage. The story of Prophet Yusuf Alaihi Salam is an interesting story to discuss because it has moral messages. This story is synonymous with his patience, determination, faith, morals and sincerity in controlling himself, educating those around him, nurturing the people of Egypt and teaching how to behave when he was a persecuted ordinary person to become a palace dignitary.